Altered pancreas remodeling following glucose intolerance in pregnancy in mice. Issue 2 (May 2020) - Szlapinski, Sandra K; Botros, Anthony A; Donegan, Sarah; King, Renee T; Retta, Gabrielle; Strutt, Brenda J; Hill, David J
Abstract : Gestational diabetes mellitus increases the risk of dysglycemia postpartum, in part, due to pancreatic β-cell dysfunction. However, no histological evidence exists comparing endocrine pancreas after healthy and glucose-intolerant pregnancies. This study sought to address this knowledge gap, in addition to exploring the contribution of an inflammatory environment to changes in endocrine pancreas after parturition. We used a previously established mouse model of gestational glucose intolerance induced by dietary low protein insult from conception until weaning. Pancreas and adipose samples were collected at 7, 30 and 90 days postpartum for histomorphometric and cytokine analyses, respectively. Glucose tolerance tests were performed prior to euthanasia and blood was collected via cardiac puncture. Pregnant female mice born to dams fed a low protein diet previously shown to develop glucose intolerance at late gestation relative to controls continued to be glucose intolerant until 1 month postpartum. However, glucose tolerance normalized by 3 months postpartum. Glucose intolerance at 7 days postpartum was associated with lower beta- and alpha-cell fractional areas and higher adipose levels of pro-inflammatory cytokine, interleukin-6. By 3 months postpartum, a compensatory increase in the number of small islets and a higher insulin to glucagon ratio likely enabled euglycemia to be attained in the previously glucose-intolerant mice. The results show that impairments in endocrine pancreas compensation in hyperglycemic pregnancy persist after parturition and contribute to prolonged glucose intolerance. These impairments may increase the susceptibility to development of future type 2 diabetes.